Transport Behavior in Polymer-Inorganic Membrane: A Review - Nik Mustofar, N. N.; Jaafar, Juhana; Aziz, M.; Ismail, A. F.; A. Rahman, Mukhlis; Othman, M. H. D.; Yusof, N.; Salleh, W. N. W.; Aziz, F.; Rosmi, M. S. (Journal of Applied Membrane Science & Technology, 2017)
The polymer–inorganic composite membrane has emerged as an alternative to improve the separation properties of polymer membranes because they possess properties of both organic and inorganic membranes such as good hydrophilicity, selectivity, permeability, mechanical strength, and thermal and chemical stability. A unique combination of organic and inorganic properties is believed could overcome the limitations of the pure polymeric membranes. Transport behavior of gases, vapours and liquids through polymer membranes are important in ultrafiltration, nanofiltration, pervaporation, gas separation and fuel cell applications. A better understanding of transport mechanisms in polymer-inorganic composite membranes is highly important in order to achieve significant achievement in the respective applications. This article provides a detailed review of current research in the field of transport phenomena on the transport behaviour of proton and methanol through the polymeric-inorganic by means of proton conductivity and methanol permeability.